Illuminationist texts and textual studies essays in memory of Hossein Ziai - Gheissari, Ali 1954-; Walbridge, John 1950-; Alwishah, Ahmed (Brill, 2018)
The late Professor Hossein Ziai's interests focused on the Illuminationist (Ishrāqī) tradition. Dedicated to his memory, this volume deals with the post-Avicennan philosophical tradition in Iran, and in particular the Illuminationist school and later philosophers, such as those associated with the School of Isfahan, who were fundamentally influenced by it. The focus of various chapters is on translations, editions, and close expositions of rationalist works in areas such as epistemology, logic and metaphysics rather than mysticism more generally, and also on specific texts rather than themes or studies of individual philosophers. The purpose of the volume is to introduce new texts into the modern canon of Islamic and Iranian philosophy. Various texts in this volume have not been previously translated nor have they been the subject of significant Western scholarship